Стан і проблеми нормативно-правового поля формування соціально-відповідальної поведінки фармацевтичних фахівців (освітній та спеціальний рівень) - Ткаченко, Наталя Олександрівна; Громовик, Б. П.; Алексєєв, Олександр Германович; Tkachenko, N. O.; Hromovyk, B. P.; Aleksieiev, O. G. (My University, 2018)
Мета роботи. Визначення повноти і змістовності чинної нормативно-правової бази (НПБ) освітнього і спеціального рівня моделі правового поля формування системи соціально-відповідальної поведінки (СВП) фармацевтичних фахівців (ФФ), а також опрацювання пропозицій щодо оптимізації зазначеної НПБ. Матеріали і методи. Матеріалом дослідження були нормативно-правові акти (НПА), які регламентують СВ, фармацевтичну освіту та діяльність ФО. У роботі використано методи інформаційного пошуку, систематизації, контент-аналізу, порівняння та узагальнення. Результати й обговорення. Проаналізовано НПБ моделі правового поля формування системи СВП ФФ упродовж всього життєвого професійного циклу за двома критеріями: ієрархічним принципом (Закони України, Постанови КМ України, накази МОЗ України) та регулюванням відносин у системі СВП ФФ на освітньому і спеціальному рівнях. Окреслено проблемні питання зазначеної НПБ та визначено заходи з її вдосконалення. Висновки. На підставі аналізу НПА різної ієрархії визначені проблемні питання у правовому полі на освітньому та спеціальному рівнях формування СВП ФФ, що зумовлюють труднощі ефективної реалізації СВ ФО. Сформульовано заходи щодо вдосконалення НПБ щодо регулювання діяльності фармацевтичної галузі та формування СВП усіх її суб’єктів. Objective: determination of the completeness and content of the current regulatory and legal framework of the educational and special levels of the model of the legal field for the formation of a system of socially responsible behavior of pharmacists, and the development of proposals for the optimization of this regulatory framework. Materials and methods. The material for the study was normative legal acts regulating social responsibility, pharmaceutical education and activities of pharmaceutical organizations. In the course of our work we used the methods of information retrieval, systematization, content analysis, comparison and generalization. Results and discussion. We have analyzed the legal framework of the model of the legal field for the formation of socially responsible behavior of pharmacy specialists throughout the life cycle of professional development for two criteria: hierarchical principle (Laws of Ukraine, Decrees of the Cabinet of Ministers of Ukraine, orders of the Ministry of Health of Ukraine) and regulation of relations in the system of socially responsible behavior of pharmacy specialists at the educational and special levels. We have identified a number of problematic issues of this regulatory framework and measures to improve it. Conclusions. Based on the analysis of regulatory legal acts of different hierarchies, we identified problematic issues in the legal field at the educational and special levels of the formation of socially responsible behavior of pharmacists. We have formulated measures to improve the regulatory and legal framework for regulating the activities of the pharmaceutical industry and the formation of socially responsible behavior of all its subjects.
The state and problems of the normative-legal field of forming social and responsible behavior of pharmacy specialists (educational and special level)
Состояние и проблемы нормативно-правового поля формирования социально-ответственного поведения специалистов фармации (образовательный и специальный уровень)
Keywords: соціальна відповідальність; фармацевтичний фахівець; фармацевтична організація; фармацевтична діяльність; нормативно-правові акти; social responsibility; pharmacists; pharmaceutical organization